Trabajo en equipo y desarrollo del pensamiento crítico en la formación docente en la Universidad Nacional Daniel Alcides Carrión, pasco, perú - Carhuaricra Meza, Julio César (2019)
Working in teams and the development of critical thinking are capabilities that we must promote in university students, as proposed by the latin america tuning project. Guided by such demand we set out to determine the influence of the first (t .e.) upon the second one (P.c.) in the context of teacher training. We have selected a correlative and explanatory study type, the design chosen is the quasi - experimental, with multiple treatments with evaluations of pre test and post test. at the same time, we considered two groups: experimental and control. The universe was constituted of 753 alumni and the sample of 60 alumni. The applied techniques were: for the samples, not probabilistic with finite population; for the data collection survey and documentary analysis. The main conclusion reached by this investigation is that teamwork influences favorably in the development of critical thinking in the teacher training.